2022
DOI: 10.1021/acs.langmuir.2c00015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electric Fields on Silicon-Based Monolayers

Abstract: Electric fields can induce bond breaking and bond forming, catalyze chemical reactions on surfaces, and change the structure of self-assembled monolayers on electrode surfaces. Here, we study the effect of electric fields supplied either by an electrochemical potential or by conducting atomic force microscopy (C-AFM) on Si-based monolayers. We report that typical monolayers on silicon undergo partial desorption followed by the oxidation of the underneath silicon at +1.5 V vs Ag/AgCl. The monolayer loses 28% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…5 mg) of ammonium sulfite was added to scavenge oxygen. This process leads to a hydrogen-terminated Si surface [Si(111)–H]. The etched samples were rinsed sequentially with Milli-Q water and dichloromethane and were then blown dry in a stream of argon before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…5 mg) of ammonium sulfite was added to scavenge oxygen. This process leads to a hydrogen-terminated Si surface [Si(111)–H]. The etched samples were rinsed sequentially with Milli-Q water and dichloromethane and were then blown dry in a stream of argon before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Important to consider is the possible irreversible negative effect an electric field may have on the biomolecular layer and its functionality. Li et al [ 130 ] studied the effect of an applied electric field on self-assembled monolayer of organic molecules on oxide-free silicon surfaces. They reported that typical monolayers on hydrogen-terminated silicon undergo partial desorption followed by the oxidation of the underneath silicon at +1.5 V vs Ag/AgCl.…”
Section: Current Trends In Biosensors Assisted By Dielectrophoresismentioning
confidence: 99%
“…It was shown that typical monolayers on hydrogen-terminated silicon undergo partial desorption followed by the oxidation of the underneath silicon at +1.5 V vs. Ag/AgCl. Furthermore, the monolayer lost 28% of its surface coverage and 55% of its electron transfer rate after 10 min [ 130 ]. Detaching of receptor molecules as well as conformational changes of receptors or analytes could be important limitations.…”
Section: Perspectives and Challengesmentioning
confidence: 99%
“…These sites are reactive toward oxygen and water and initiate an oxidation of the silicon surface. 39 The oxide layer grows on the surface of the silicon atoms and in between the Si atoms of the surface, changes Si−Si bond angles, breaks bonds, and extends inside the bulk Si structure. The mechanism of oxidation of Si surfaces is a subject of continuous debate.…”
Section: Introductionmentioning
confidence: 99%